KEBIJAKAN PEMERINTAH DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN MUSI RAWAS - hartawan hartawan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
This study attempts to look at attentively the local government of kabupaten musi rawas with an organization device was over all the country policies in the preparation of the issuing of the direction of poverty reduction programs .The results of research that is chronic: poverty caused: ( 1 ) a posture and habits of the lives of the community that is unproductive; ( 2 ) the limited means and their isolation; and ( 3 ) low level of the economic situation of education and of health care , the limited job opportunities , the community and helplessness , and poverty while caused ( 1 ) amendments to the economic cycle than in the normal situation be the economic crisis; ( 2 ) seasonal change by poverty such as the cases of food crops; and ( 3 of natural disaster or impact of a policy